2020
DOI: 10.1038/s41423-020-00557-9
|View full text |Cite
|
Sign up to set email alerts
|

Unique immunological profile in patients with COVID-19

Abstract: The relationship between severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) and host immunity is poorly understood. We performed an extensive analysis of immune responses in 32 patients with severe COVID-19, some of whom succumbed. A control population of healthy subjects was included. Patients with COVID-19 had an altered distribution of peripheral blood lymphocytes, with an increased proportion of mature natural killer (NK) cells and low T-cell numbers. NK cells and CD8+ T cells overexpressed T-cel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
185
2
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 223 publications
(209 citation statements)
references
References 37 publications
16
185
2
6
Order By: Relevance
“…A study that described detailed responses of NK cell to SARS-CoV-2 infection, showed that increased proportions of a subset of NK cell types called adaptive NK cells are found in severe but not moderate COVID-19 disease (55,79). The absolute numbers of NK cells were lower in the blood of patients with COVID-19 compared with healthy controls, consistent with other reports.…”
Section: The Dynamics Of a Contracting And Expanding Nk Population Insupporting
confidence: 86%
“…A study that described detailed responses of NK cell to SARS-CoV-2 infection, showed that increased proportions of a subset of NK cell types called adaptive NK cells are found in severe but not moderate COVID-19 disease (55,79). The absolute numbers of NK cells were lower in the blood of patients with COVID-19 compared with healthy controls, consistent with other reports.…”
Section: The Dynamics Of a Contracting And Expanding Nk Population Insupporting
confidence: 86%
“…2F) 44,46,47 . There were transcriptional changes associated with exhaustion, such as decreased expression of KLRG1 and SIGLEC7 48 . DGE in NK cells between cases and controls were enriched for genes related to the interferon-alpha response, regulation of NK cell cytokine production, and viral transcription (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…They still, however, claim their findings suggest that T-cell activation and exhaustion play a role in Covid-19 and posit T-cell targeted treatment options may be of interest (16). Varchetta et al report an increase in TIM-3 and CD69 expression in CD8+ T cells and note the extent of CD8+ T cell lymphopenia was significantly greater in patients that succumbed to Covid-19 (17). They describe this as a hyperactivated/exhausted state and observed that during recovery TIM-3 and CD69 expression on T cells fell and CD8+ lymphocyte count rose.…”
Section: Dissecting Possible T Cell Migration "Exhaustion" and Endmentioning
confidence: 99%
“…They describe this as a hyperactivated/exhausted state and observed that during recovery TIM-3 and CD69 expression on T cells fell and CD8+ lymphocyte count rose. They offer TIM-3, PD-1, and NKG2A as "druggable molecules" that may be used to "unleash antiviral activity" (17).…”
Section: Dissecting Possible T Cell Migration "Exhaustion" and Endmentioning
confidence: 99%